Spontaneous hepatica rupture in the puerpera without pregnancy hypertensive disease or liver disease: Case report - Guevara-Ríos, Enrique (2023)
Liver rupture is a serious complication of pregnancy with high morbidity and mortality, it is frequently related to preeclampsia; exceptionally it can occur in a pregnant woman without preeclampsia or HELLP syndrome. There is a case of a pregnant woman without preeclampsia or previous liver disease who develops a liver rupture in the puerperium, she is promptly diagnosed and surgically managed. The patient evolved favorably.